2018
DOI: 10.1136/ebmental-2018-300061
|View full text |Cite
|
Sign up to set email alerts
|

Ultra-high-risk paradigm: lessons learnt and new directions

Abstract: Within the embryonic early psychosis field in the early 1990s, the conceptualisation and definition of an at-risk or ultra-high-risk (UHR) mental state for psychosis was a breakthrough which transformed the clinical and research landscape in psychiatry. Twenty-five years later, we have a new evidence base that has illuminated the neurobiology of the onset phase of psychotic disorder, delivered Cochrane level 1 evidence showing that the onset of full-threshold sustained psychotic disorder can be at least delaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
38
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 36 publications
0
38
0
1
Order By: Relevance
“…Following our critical perspective papers on the CHR concept 3,5 , an intense debate has started, splitting the field into proponents 6‐8 , opponents 9‐12 , and those with ambivalent attitudes toward that concept 13‐16 .…”
mentioning
confidence: 99%
“…Following our critical perspective papers on the CHR concept 3,5 , an intense debate has started, splitting the field into proponents 6‐8 , opponents 9‐12 , and those with ambivalent attitudes toward that concept 13‐16 .…”
mentioning
confidence: 99%
“…McGorry and his colleagues have already proposed a pluripotent prospective program that reflects this concept. The CHARM study encompasses schizophrenia, mood disorder, and borderline personality disorder outcomes and implements a clinical staging model along the mental health continuum (57). The CHARM study will also provide predictive and discriminant validity of the proposed criteria 16.…”
Section: Discussionmentioning
confidence: 99%
“…In reality, it is likely that several phenotypic pathways leading to FEP exists outside of the UHR paradigm (e.g. in patients in which early psychotic symptoms may be absent) [40,63]. Furthermore, if a proportion of the UHR patients is not detected this would mean a reduction in the demonstrated benefits.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with UHR demonstrate certain levels of intensity, severity and/or pathognomonic symptoms (e.g. a Global Assessment of Functioning-score <70) [40]. The development of this staging model in which the importance of identification and treating patients at UHR for psychosis was emphasized, boosted an interest in preventive psychiatry and it has been demonstrated that early detection and intervention in people at ultra-high risk of developing psychosis can be successful to prevent or delay a first psychosis [40][41][42].…”
Section: Introductionmentioning
confidence: 99%